2020
DOI: 10.1093/ageing/afaa201
|View full text |Cite
|
Sign up to set email alerts
|

SEekingAnsweRs forCareHomes during the COVID-19 pandemic (COVID SEARCH)

Abstract: The care and support of older people residing in long-term care facilities during the COVID-19 pandemic has created new and unanticipated uncertainties for staff. In this short report, we present our analyses of the uncertainties of care home managers and staff expressed in a self-formed closed WhatsApp™ discussion group during the first stages of the pandemic in the UK. We categorised their wide-ranging questions to understand what information would address these uncertainties and provide support. We have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 6 publications
1
46
0
Order By: Relevance
“…Recently there has been evidence that care homes may be prepared to work in a more concerted way as a sector when they engage with research networks(28) and in regional improvement programmes(29). The findings presented here build on those from other studies conducted during the pandemic(19) which showed have shown the preparedness of care home providers to work together not only to provide peer-support, but also advice and expertise, and even critical supplies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Recently there has been evidence that care homes may be prepared to work in a more concerted way as a sector when they engage with research networks(28) and in regional improvement programmes(29). The findings presented here build on those from other studies conducted during the pandemic(19) which showed have shown the preparedness of care home providers to work together not only to provide peer-support, but also advice and expertise, and even critical supplies.…”
Section: Discussionsupporting
confidence: 78%
“…We supplemented this by asking professional care and research networks to publicise the study using social media and electronic mailing lists. We chose to focus on managers new to research because many care home managers that we had routinely interacted with in the past through our research had engaged with online support forums alongside senior clinicians and academics(19). We considered that such experiences were likely to be atypical and we wished to explore broader accounts of how care homes responded to the pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…Between July and August 2020, care home staff members were contacted through a national online COVID-19 peer-support group for care home managers and staff [ 8 ] and then recruited to take part in semi-structured interviews. Purposive sampling was used to ensure the opinions elicited were representative of a range of organisational factors (care home size, residential/nursing, independent operator/chain) that have been shown to influence the severity of outbreaks during the pandemic [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…The second, in 2007, proposed a classification of 5 levels [ 4 ]. And the more recent one, in 2009, developed a 6-level classification [ 5 ], and has been recently used in relevant research [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%